Immunological response and match performance of professional tennis players of different age groups during a competitive season - Kozlowska, M.; Zurek, P.; Rodziewicz, E.; Góral, K.; Zmijewski, P.; Lipinska, P.; Laskowski, R.; Walentukiewicz, A. K.; Antosiewicz, J.; Ziemann, E. (The Journal of Strength and Conditioning Research, 2021)
We aimed to investigate the effect of physical workloads on immunological response, match performance, and iron metabolism in professional tennis players of different age groups throughout the tournament season and to determine the interdependence of vitamin D status and inflammation. Thirty-eight young, male tennis players with a top national ranking (1-25) participated in this study and were assigned to the following age groups: cadets (CG), juniors (JG), and seniors (SG). Blood samples were collected at the beginning, midpoint, and end of the tournament season to assess the proinflammatory cytokine (tumor necrosis factor—alpha [TNF-a]), anti-inflammatory myokines (interleukin [IL]-6 and IL-10), heat shock proteins (HSP70, HSP27), iron metabolism markers, and vitamin D concentrations. The total number of matches (won and lost) at the national and international events was recorded. The IL-6 and IL-10 concentrations significantly increased across all groups in the middle and end of the tournament season (effect large and very likely). The TNF-a concentration was elevated at the end of the season in CG and SG. The increase in TNF-a concentration corresponded with an increase in hepcidin concentration in these groups. The significant increase in HSP27 concentration was only noticed in SG with normal vitamin D concentrations. In JG and SG, a mild seasonal increase in vitamin D concentration was noted, but still it was insufficient. The immunological response was not affected by the number of tennis matches; however, the anti-inflammatory effect was regulated by higher concentrations of vitamin D. Unexpectedly, most tennis players had vitamin D deficiency. Iron status remained unchanged.